Logical model of mobile object control (Nexo Revista Científica, 2021)
This paper describes a logical model applied as a soft control tool to mobile objects. The model of the logical spatial situation without uncertainty, i.e., according to the law of excluded middle, is considered as the basis. Nonetheless, the motion rules are derived using an approach applied in constructible mathematics and logic. The approach consists in the finitude of variants of control and analyzing all potential traffic scenarios. The constructible object considered in this paper is the situation’s logical model. The constructible approach consists in considering the model of a typical railway station by the example of which the traffic is analyzed. The situation’s logical model is implemented as a condition for potential traffic. This model is described using mathematical logic with the help of logical variables and rules. The control system in this case makes use of permissible versions of logical designs. The control relies on the feasibility of traffic. The system of control rules is developed on the basis of the logical situation’s model and formed without uncertainty. The article provides an analysis of complementary kinds of traffic.